Formalizing the informal settlements in Kathmandu valley: A case of Bansighat along Bagmati river corridor - Karki, Bibek; Singh, Sangeeta (Journal of Innovations in Engineering Education, 2022)
Informal settlements are residential areas where housing is developed without land title and tenure. Housing developed with land tenure within the realms of rules and regulations are formal housing. As the settlements are termed informal, there are no formal programs from the concerned government agencies to develop infrastructure. This does not limit the settlers to develop the basic infrastructures they essentially need. Policies in the recent years have tried to address the issues of informal settlers. There is a gap between activities and policies of the government which is identified by policy review. This research is a study of the assessment of infrastructure and services in informal settlements and how the gap in infrastructure can be addressed. Based on observation, key informant interview and questionnaire survey, this research assesses the existing scenario of infrastructure reach and attempts to address the infrastructure gap through physical intervention and policy intervention in Bansighat informal settlement along Bagmati River Corridor. The research thus uses mixed methods to frame the current scenario and propose recommendations suitable to the place. The gaps are seen majorly in water supply, drainage, housing, roads and educational, general awareness sectors. Alternatives for addressing the gaps is through co-ordination among different levels of government with implementation of plans by local government which are prepared by line agencies from federal and provincial governments. Physical interventions are needed in basic infrastructures: drinking water, storm water drainage, road width and density of housing in Bansighat. Awareness of social infrastructure like education is also needed in the area. These interventions should be guided and supported by policy measures and participative implementation to provide infrastructure in Bansighat and similar informal settlements along Bagmati corridor in Kathmandu valley.